2020
DOI: 10.1073/pnas.1907493117
|View full text |Cite
|
Sign up to set email alerts
|

Multiple metastable network states in urban traffic

Abstract: While abrupt regime shifts between different metastable states have occurred in natural systems from many areas including ecology, biology, and climate, evidence for this phenomenon in transportation systems has been rarely observed so far. This limitation might be rooted in the fact that we lack methods to identify and analyze possible multiple states that could emerge at scales of the entire traffic network. Here, using percolation approaches, we observe such a metastable regime in traffic systems. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 31 publications
(30 reference statements)
0
44
1
Order By: Relevance
“…However, we did not find these meta-stable states and each measure of the size of the GC as a function of occupancy is close to the average relation displayed in figure 3b. The most likely explanation for this discrepancy is that our measures are averaged over an hour, which is a long period of time compared with the typical stability duration of the metastable states found in [20], which is of order 10 minutes. This suggests that our measure thus only reflects the average of the systems oscillations between the two states.…”
Section: Giant Componentmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we did not find these meta-stable states and each measure of the size of the GC as a function of occupancy is close to the average relation displayed in figure 3b. The most likely explanation for this discrepancy is that our measures are averaged over an hour, which is a long period of time compared with the typical stability duration of the metastable states found in [20], which is of order 10 minutes. This suggests that our measure thus only reflects the average of the systems oscillations between the two states.…”
Section: Giant Componentmentioning
confidence: 94%
“…We find that the congestion percolates during rush hours and the dependence of the average giant component size on the average occupancy rate displays a typical shape of percolation in a finite size system, as displayed in figure 3a. Zeng et al [20] have shown that during rush hours the network oscillates between multiple meta-stable states: for a given fraction of congested links, they found that there could either be a giant functional cluster or several small functional clusters. We tried to reproduce these results for our case of the cluster of congestion rather than functional clusters.…”
Section: Giant Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting empirical evidence suggesting the hypotheses that urban networks exhibit self-organized criticality (SOC) (Zeng et al, 2019, Zhang et al, 2019, Zeng et al, 2020, Bak et al, 1987, a celebrated paradigm in the 90's that has proved very useful in countless areas of science, from earthquakes to stock prices to forest fires to astrophysics (Dȃnilȃ et al, 2015, Aschwanden, 2014. Despite being around for 2 or 3 decades now, the theory and control consequences of SOC have not permeated the transportation literature.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on the network assumes that the network is static, while many real systems dynamically evolve. For example, traffic networks with flow changes over time [16], while friendship networks decreased in size with time increasing [17]. For some systems in real-world scenarios, after the collapse, they can spontaneously recover.…”
Section: Introductionmentioning
confidence: 99%